Mucinous cystic tumour of low malignant potential presenting in a patient with prior non-seminatous germ cell tumour - Chahal, Daljeet; Martens, Mildred; Kinahan, John (Canadian Urological Association Journal, 2015)
Urachal neoplasms are rare entities which may be classified as cystic or non-cystic. Literature surrounding patient outcomes remains limited to non-cystic, urachal adenocarcinomas. Literature focusing on mucinous cystic neoplasms of the urachus is sparse. These mucinous cystic lesions may be subclassified as benign mucinous cystadenomas, mucinous cystic tumours of low malignant potential, and mucinous cystadenocarcinomas. Mucinous subtypes have the potential to behave aggressively and may result in pseudomyxoma peritonei. We describe here the case of a 37-year-old male with a mucinous cystic tumour of low malignant potential after prior right orchiectomy and left hydrocelectomy. This case raises the interesting possibility of multiple genitourinary neoplasms arising in a similar time frame.